Adsorption of methanol on highly graphitized thermal carbon black effects of the configuration of functional groups and their interspacing. (July 2017) - Klomkliang, Nikom; Nantiphar, Orathai; Thakhat, Sarita; Horikawa, Toshihide; Nakashima, Kouki; Do, D.D.; Nicholson, D.
Abstract: Adsorption of methanol on a carbon black has been studied to investigate the effects of the separation distance and orientation of two functional groups on the adsorption isotherm and the isosteric heat. Monte Carlo simulation was carried out to study methanol adsorption on a graphene surface with two hydroxyl groups arranged in three different orientations: (1) outward, (2) co-directional, and (3) inward. Depending on the orientation and the spacing, the isosteric heat at zero loading is either greater or less than the heat of condensation, highlighting the importance of the interplay between the spacing and the orientation. As the loading is increased to the stage where the functional groups have been covered, methanol begins to adsorb on the graphite surface because of the methyl group-graphite interaction and the large surface area of graphite. At higher loadings adsorption proceeds by molecular layering on the graphite surface, and the isosteric heat approaches the heat of condensation, implying that the multilayered methanol has a structure similar to the bulk fluid. The simulation results for the isotherm and for the isosteric heat versus loading are in agreement with experimental data for methanol on Carbopack F samples. Graphical abstract: